Climate Change and Management of Cool Season Grain Legume Crops - Yadav, Shyam Singh; McNeil, David L.; Redden, Robert; Patil, Sharanagouda A. (Springer Netherlands : Imprint: Springer, 2010)
Legumes are a major source of food, nutrition and feed worldwide particularly in developing nations. Climate change is likely to exacerbate the effects of heat and drought stress in the future as well as push legumes production into more marginal lands. The goal of this book is to present an analysis of the production and science issues we are likely to face now and in the future. This book covers all aspect of legume production management technologies, plant ecological response, nutrients management, biological nitrogen fixation, molecular approaches, potential cultivars, biodiversity management under climate change. Also covered are various aspects of legume management under climate change and include; Production management technology, ecology & adaptation, diseases, and international trade. Physiology and crops response to nutrients, drought, salinity, and water use efficiency. Biodiversity management, molecular approaches and biological Nitrogen fixation. Climate change and strategies This book presents the most comprehensive and up to date review of research on different cool season grain legume crops, nutrients management, biotic and abiotic stresses management, agronomical approaches for drought management, salinity, drought, weed management and water use efficiency, impact on international trade around the world. This book will be of great value to legume breeders, grain producers, agronomists, scientists, academic researchers, graduates students, traders, and farmers in the developing and the developed world.